Effects of smoking on the severity and transmission of pulmonary tuberculosis: A hospital-based case control study - Yanmei Feng; Yue Xu; Yuan Yang; Guangzhao Yi; Huan Su; Hong Chen; Rui Guo; Jinwei Jia; Pu Wang (Frontiers Media S.A., 2023)
IntroductionThere is a high incidence of both smoking and tuberculosis (TB) in China. This study examined the risk factors for severe pulmonary TB (PTB) and positive tubercle bacilli in sputum.MethodsWe conducted a retrospective case-control study in a tertiary hospital from January 2017 to December 2018 (n = 917). The clinical and biological characteristics of patients were collected, and univariable and multivariable logistic regression analyses were performed to assess the factors associated with smoking in terms of the severity and transmission of PTB.ResultsPositive tubercle bacilli in sputum and severe PTB were much higher in smoking patients. Together with nutrition status, heavy smoking exhibited a 284% greater risk in severe PTB. Positive tubercle bacilli in sputum was significantly associated with hypoproteinemia and smoking regardless of the status, duration, and degree.ConclusionBecause cigarette smoking was strongly and inversely associated with hypoproteinemia, we conclude that smoking plays a critical role in the severity and transmission of PTB. Smoking cessation interventions should be employed to prevent severe PTB and decrease the transmission of PTB.